Knowledge of symptoms and self-management of hypoglycaemia amongst patients attending a diabetic clinic at a regional hospital in KwaZulu-Natal - Anthony Ejegi; Andrew John Ross; Keshena Naidoo (AOSIS, 2016)
Background: Diabetic patients on insulin and sulphonylureas are at risk of developing hypoglycaemia. Many patients do not respond appropriately because of poor knowledge and understanding of the symptoms of hypoglycaemia, which if not promptly treated can lead to permanent neurological and renal damage. Hypoglycaemic complications can be avoided if patients have a good knowledge of the early symptoms of hypoglycaemia and know how to respond appropriately. Aim: The aim of this study was to assess the knowledge of adult diabetic patients attending a diabetic clinic about symptoms of hypoglycaemia and how they responded to these symptoms. Setting: A hospital-based diabetic clinic in northern KwaZulu-Natal. Methods: This was a cross-sectional, descriptive study involving 200 diabetic patients. Demographic data and details of current medication, knowledge of hypoglycaemia and how patients responded to the symptoms were collected using a validated questionnaire. Results: The majority of the patients had fair to good knowledge of hypoglycaemia; however, less than 25% knew what action to take when they experienced symptoms suggestive of hypoglycaemia. Conclusion: There is a need to improve the education given to diabetic patients on stepwise measures to take to avoid life-threatening complications associated with hypoglycaemia.